CONVERSATION VERSES OF SURAH AL-KAHF’S TRANSLATION: A COOPERATIVE PRINCIPLE PERSPECTIVE - Muhammad Saibani Wiyanto; Lucky Ayu Novitasari (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2019)
This research is aimed to describe the cooperative principle in conversation verses of Surah Al-Kahf’s Translation composed by Marmaduke Pickthall. This research is qualitative research, within using document analysis as the approach. The research finding showed that four maxims were used. They are maxim of quantity, maxim of quality, maxim of relation, and maxim of manner. The most frequent data is maxim of manner, occurred in 12 utterances of conversation verses. Whilst, the least data is maxim of quantity, observed once, that is in 1 utterance of conversation verses only. The utterances of conversation verses could be explained related to maxims meaning or perspective. and the phrase expressions found based on maxim contain meanings which are interrelated with the meaning of each maxim itself. The cooperative principle contributes to maxims in conversational verses of Surah Al-Kahf’s Translation which is created by Marmaduke Pickthall.